The Use of Social Media in Improving Investment Literacy in Islamic Mutual Funds - Angelina Isnaini; Rachmanda Arsyil Majid; Nabilatul Mardliyyah (FEBI UIN Sunan Kalijaga Yogyakarta, 2023)
Reksadana Syariah are a forum for raising public funds which are managed by a legal entity called an Investment Manager, to then be invested in securities such as: stocks, bonds and money market instruments in accordance with the provisions and principles of Islamic sharia, including a portfolio of fund placements. in Islamic financial instruments such as Islamic stocks and sukuk. Islamic mutual funds can only invest in financial securities that are in accordance with sharia rules and principles, and of course they are still bound by investment restrictions set by the OJK. Securities that are classified as sharia are included in the List of Sharia Securities issued by OJK. Reksadana Syariah are still bound by Islamic Sharia rules which are based on the Koran. Reksadana Syariah have a supervisor called the Sharia supervisory board whose job is to supervise, provide advice, give consideration to the use of social funds, as well as education, promotion and product development. The community itself is not very familiar with what exactly Reksadana Syariah are and the rules contained therein. In this journal it can be seen how Reksadana Syariah are managed in accordance with existing rules.